Pengaruh Penambahan Ekstrak Bunga Sepatu (Hibiscus rosa sinensis Linn.) Terhadap Peningkatan Aktivitas Antioksidan, Total Flavonoid, dan Warna Pada Mie Kering Berbahan Mocaf - Toke, Mersiana P; Prabowo, Sulistyo; Saragih, Bernatal; Banin, Maghfirotin M (Universitas Pattimura, 2024)
Dry noodles are a popular type of noodle, but product innovation needs to be carried out to promote food diversity. Hibiscus flower extract can be used not only as a natural coloring agent but also for its health benefits, such as antioxidant activity and total flavonoids. The aim of the research was to identify the effect of adding hibiscus extract to dry noodles on antioxidant activity, total flavonoids, moisture content and color. A non-factorial Completely Randomized Design with five treatments and three replications was used. The ratio of hibiscus extract was 5, 10, 15, 20 and 25% with a wheat flour and mocaf ratiom of 60:40. Mocaf was used in this product because it is affordable, widely available, and gluten free. The result of ANOVA (5% level) and Tukey’s test using Graphpad software showed that the addition of hibiscus extract to dry noodles had a significant effect on all test. The antioxidant activity in the best treatment, with 25% hibiscus extract was 47.482%, which was classified as very strong. The total flavonoids in the best treatment with 25% hibiscus extract was 147.14 mgQE/g, The mositure content ranged between 2.95-7.68% (meeting standards of SNI 01-8217-2015). The color of the dry noodles ranged from 0.34-1.44, with differences classified from not clearly visible to very small.